Social Justice in the Welfare of Private Lecturers: A Legal Review of Salaries, Certification, and BPJS Ketenagakerjaan in Indonesia - Harahap, Arifuddin Muda; Ahyani, Hisam; Miftakhul Huda; Naeli Mutmainah; Naelul Azmi; Sérgio António Neves Lousada (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
This article discusses the issue of the welfare of private lecturers in Indonesia from a legal perspective, focusing on three main aspects: salaries, certification, and social security through BPJS Ketenagakerjaan. In the context of social justice, this study identifies the challenges faced by private lecturers related to the provision of salaries that are not in accordance with the Regional Minimum Wage (UMR), delays in lecturer certification, and the lack of adequate social protection through BPJS Ketenagakerjaan. This study uses a qualitative approach by interviewing lecturers at various private universities in Indonesia, spread across 5 provinces (West Java, Central Java, East Java, North Sumatra, and Bengkulu) and in 12 cities/regencies. The total campuses that are the objects of this study are 24 private universities, consisting of universities, institutes, and colleges. Legal analysis is carried out on existing regulations related to lecturer welfare. The results of the study show that although there are regulations governing the welfare of lecturers, inconsistent implementation has caused injustice felt by many private lecturers. This article suggests the need to revise and strengthen legal regulations to ensure the rights of private lecturers in Indonesia are fulfilled, in order to achieve equitable welfare.